Thermodynamics of B-Z transition in supercoiled DNA. - Sen, S (1987)
The nature of the possible supercoil-induced B-Z transition has been analyzed from the thermodynamical point of view, by taking into account the effects of the twisting as well as the writhing components of the supercoiling free energy. The cooperative aspects of the transition, as predicted by theory, agrees well with the corresponding experimental data.